Qili Qiangxin ameliorates chronic heart failure: a randomized clinical trial of biomarkers, inflammation, and cardiac outcomes - Zhu, Feng; Hu, Rui; Lv, Chao; Wang, Jin; Du, Xuqin; Zeng, Xudong; Huang, Yuxuan; Ma, Yiming; Yang, Cheng; Guo, Fengjie (Frontiers in Pharmacology, 2025)
ObjectiveTo evaluate the effects of the Chinese botanical formulation Qili Qiangxin (QLQX) on clinical outcomes, cardiac function, systemic inflammation, and intestinal permeability in patients with chronic heart failure (CHF).MethodsIn a randomized, controlled, parallel-group trial, 110 patients with CHF were assigned to receive QLQX plus standard-of-care (n = 55) or standard-of-care alone (n = 55); 101 participants completed follow-up. Clinical assessments included New York Heart Association (NYHA) functional classification, Minnesota Living with Heart Failure Questionnaire (MLHFQ) scores, and echocardiography. Serum B-type natriuretic peptide (BNP), tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), trimethylamine-N-oxide (TMAO), D-lactate (D-LA), and intestinal fatty acid-binding protein (I-FABP) were measured to assess systemic inflammation and intestinal barrier injury. Correlation between biomarker levels and CHF severity indices were examined.ResultsCompared with control, the QLQX exhibited significant improvements in NYHA class (p < 0.05) and MLHFQ scores. The QLQX group showed significant reductions in BNP, TNF-α, IL-6, and TMAO (p < 0.01), indicating attenuation of systemic inflammation. D-LA and I-FABP were significantly lower with QLQX (p < 0.05), suggesting improved intestinal barrier integrity. Higher levels of TMAO, TNF-α, IL-6, D-LA, and I-FABP correlated with worse NYHA class and lower left ventricular ejection fraction (LVEF) (p < 0.05), supporting their association with CHF severity.ConclusionAs an adjunct to standard therapy, QLQX improved clinical status and quality of life in CHF and favorably modified circulating biomarkers of cardiac stress, systemic inflammation, and intestinal barrier injury. These findings support a link between systemic inflammation, gut barrier dysfunction, and CHF severity. Larger, multicenter trials with mechanistic evaluations are needed to confirm efficacy and clarify QLQX’s molecular targets.